Aplikasi Antrian Pada Sekolah Tinggi Teknologi Pagar Alam Berbasis Web Service - Febriansyah .; Siti Aminah (Jurnal Dinamika Informatika, 2021)
This study aims to produce a Web Service-based Application for Queuing Pagar Alam High School Technology, the service system that is currently running is still done conventionally, where students have to come directly and queue long enough, because the number of students who have quite a lot of waiting chairs is becoming increasingly full, causing inconvenience in queuing. Due to the large number of queues, the lecturer staff have not been able to distinguish which students must be served first. This web service-based queuing application will later be able to help the existing service process, and students can estimate arrival time without having to wait long in the waiting chair besides that it can help staff in providing servces to be more structured. In the development of this application using the FIFO method and the Association method to determine the queue time. This system is made using PHP and MySQL programming as its database, using the waterfall SDLC method with the stages of Analysis, Design, Coding, testing and the testing method carried out in this study is Black Box Testing. With a score of 3.4 and expert review with a score of 4.2 from the implementation of beta recapitulation with a valid category. Thus the web service-based queuing application with the FIFO method and the association method can run well and validly.